Physical models of optical-electronic systems of the ir spectrum range with thermoelectric cooling (review) - Anatychuk, L.I.; Vikhor, L.M.; Matsenko, I.D. (Journal of Thermoelectricity, 2023)
The paper considers the main physical models of optical-electronic systems in the IR spectrum range with thermoelectric cooling. The features and advantages of these models are analyzed. It was established that the simplest and the one that is practically used in industrial samples of IR devices is a model of a thermoelectric module built into a metal case with photosensitive elements that are cooled. Such a model with cascade thermoelectric coolers (TEC) made of materials based on Bi2 Te3 ensures the level of operating temperatures of IR devices up to 195 K. It has been shown that expanding the cooling range to temperatures of 140-150 K is possible by using functionally graded materials and additional stages of low-temperature thermoelectric materials, for example BiSb-based materials, for TEC. It has been established that the energy efficiency of a TEC significantly depends on the optimization of its design, which should take into account the electrical and thermal resistance of contacts, interconnect and insulation plates, as well as the influence of the thermal resistance of the IR detector case, its connections with the TEC, heat sinks and heat exchangers used in the system for heat removal from TEC. Therefore, the TEC design must take into account all system components, and the choice of the physical model of the optical-electronic system with TEC is important.